Mating compatibility of wild and sterile melon flies, Bactrocera cucurbitae (Diptera: Tephritidae) treated with entomopathogenic fungi. (18th March 2013) - Sookar, P.; Bhagwant, S.; Khayrattee, F. B.; Chooneea, Y.; Ekesi, S.
Abstract Field cage tests were carried out to determine the mating compatibility of sterile and wild melon fly, Bactrocera cucurbitae (Coquillett), males that were treated or not treated with entomopathogenic fungi. The melon flies were irradiated at 70 Gy, and the adults were treated with dry conidia of either Beauveria bassiana (Balsamo) or Metarhizium anisopliae (Metchnikoff) Sorokin 1 day before the mating test. Our results demonstrate that sterile melon flies treated with either B. bassiana or M. anisopliae showed mating compatibility with the wild flies. Inoculation of the flies with the fungi did not significantly affect the mean time of copulation (323–567 min) as compared to mating involving only wild flies (407–518 min). Treatment of the flies with either B. bassiana or M. anisopliae did not significantly affect the propensity of mating. Wild females mated indiscriminately with sterile, sterile B. bassiana‐treated or sterile M. anisopliae‐treated males. Irrespective of the treatment combinations, mean percentage remating was significantly higher for sterile females with sterile males (7.72–27.12%) as compared to wild females with sterile males (0.76–14.90%). The possibility of using sterile melon flies as vectors of the entomopathogenic fungi to enhance an SIT programme is discussed.